2018
DOI: 10.1126/sciadv.aas9846
|View full text |Cite
|
Sign up to set email alerts
|

Microglial pannexin-1 channel activation is a spinal determinant of joint pain

Abstract: A new therapeutic option for treating arthritis pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 47 publications
4
65
0
Order By: Relevance
“…Large-pore forming channels play important roles in cell to cell communication by responding to diverse stimuli and releasing signaling molecules like ATP and amino acids (Giaume et al, 2013;Ma et al, 2016;Okada et al, 2018;Osei-Owusu et al, 2018). Pannexins are a family of ubiquitously expressed large-pore forming channels which regulate nucleotide release during apoptosis (Chekeni et al, 2010), blood pressure (Billaud et al, 2011;Billaud et al, 2015), and neuropathic pain (Bravo et al, 2014;Weaver et al, 2017;Mousseau et al, 2018). While pannexins have limited sequence identity with innexins (~15% identity), they have virtually no sequence similarity to other large-pore forming channels (Panchin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Large-pore forming channels play important roles in cell to cell communication by responding to diverse stimuli and releasing signaling molecules like ATP and amino acids (Giaume et al, 2013;Ma et al, 2016;Okada et al, 2018;Osei-Owusu et al, 2018). Pannexins are a family of ubiquitously expressed large-pore forming channels which regulate nucleotide release during apoptosis (Chekeni et al, 2010), blood pressure (Billaud et al, 2011;Billaud et al, 2015), and neuropathic pain (Bravo et al, 2014;Weaver et al, 2017;Mousseau et al, 2018). While pannexins have limited sequence identity with innexins (~15% identity), they have virtually no sequence similarity to other large-pore forming channels (Panchin et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The data are presented as the mean ± SD inhibition of this channel in microglia cells in mouse models can reduce neuronal pain in arteritis. 36 In another study by Diezmos et al, the expression rate of this channel was reduced in the tissues of patients with inflammatory bowel disease. 37 However, the results obtained in this study demonstrate that the expression of PANX1 gene was not significantly different between patients and healthy individuals.…”
Section: Discussionmentioning
confidence: 93%
“…Most studies on this channel have been performed in neural cells and so far, the association of this channel with diseases such as Alzheimer's, diabetes and Crohn's has been investigated . Studies have shown that inhibition of this channel in microglia cells in mouse models can reduce neuronal pain in arteritis . In another study by Diezmos et al, the expression rate of this channel was reduced in the tissues of patients with inflammatory bowel disease .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that myeloid Panx1 is critical for the progression of joint and nerve-injury pain, likely by attenuating microglial and macrophage activation at the spinal cord 41,42 . A major finding from our work is that myeloid Panx1 promotes acute infiltration of pro-inflammatory cells after brain trauma, which consequently impacts the neuroinflammatory response and outcomes after TBI.…”
Section: Discussionmentioning
confidence: 99%